2020
DOI: 10.1002/jbm.b.34564
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, characterization, and in vitro evaluation of electrospun polyurethane‐gelatin‐carbon nanotube scaffolds for cardiovascular tissue engineering applications

Abstract: Myocardial infarction occurs because coronary arteries insufficiency is one of the major causes of mortality worldwide. Recent studies have shown that tissue engineering of myocardial tissue to regenerate infarcted tissue or engineering of the coronary artery may help overcome this problem. In the present research, gelatin and single-walled carbon nanotube were firstly administrated to physico-chemically and biologically modulate polyurethane nanofibers. Electrospinning, as versatile and effective technique fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…Here again, a deep cellular infiltration into the nanofibrous scaffold was found, which would be impossible on the common flat surfaces, allowing for a larger number of attached cells per area. In addition, triple-blends including gelatin were tested for tissue engineering applications [76][77][78]. Reprinted from [66], with permission from Elsevier.…”
Section: Gelatin and Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…Here again, a deep cellular infiltration into the nanofibrous scaffold was found, which would be impossible on the common flat surfaces, allowing for a larger number of attached cells per area. In addition, triple-blends including gelatin were tested for tissue engineering applications [76][77][78]. Reprinted from [66], with permission from Elsevier.…”
Section: Gelatin and Collagenmentioning
confidence: 99%
“…Besides these often reported applications for skin or bone tissue engineering, PU blends are also used for aortic valve or cardiovascular tissue engineering [78,124,125] and other applications.…”
Section: Polyurethanementioning
confidence: 99%
“…[ 42 ] It has also been reported that PU and Gel are simultaneously dissolved in the same solution for blending, which can promote the proliferation of endothelial cells and smooth muscle cells under certain mechanical properties. [ 43 ] Compelling evidence shows that the adhesion and proliferation of endothelial cells are increased proportionately with the gelatin content in scaffolds [ 44 ]. Although numerous studies have explored the artificial blood vessels with coaxial fibers of PCL-gelatin core-shell structure, the mechanical properties of such vessels are insufficient [ 26 , 30 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It resulted in a more porous structure, however, with limited control over spatial arrangement [ 115 ]. There are several papers where CNTs are used in a composite material with PCL [ 116 , 117 ] and polyurethane [ 118 , 119 ].…”
Section: Methods Of Scaffold Fabricationmentioning
confidence: 99%